2017
DOI: 10.1212/wnl.0000000000003838
|View full text |Cite
|
Sign up to set email alerts
|

Predictive markers for early conversion of iRBD to neurodegenerative synucleinopathy diseases

Abstract: Our findings elucidate the predictive value of autonomic dysfunction and DAT uptake in identifying patients with iRBD at a high risk of progressing into neurodegenerative synucleinopathy diseases and could form a basis for future disease-prevention trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 37 publications
1
66
1
Order By: Relevance
“…The first neuroimaging marker prospectively proven to predict PD was described only as recently as 2010, when Iranzo and colleagues documented that dopaminergic functional imaging predicted neurodegeneration among patients with idiopathic RBD . This was confirmed in a second RBD cohort . Predictive value was confirmed in a non‐RBD population only in 2017, with the PARS study.…”
Section: Key Advances In the Last Decadementioning
confidence: 99%
“…The first neuroimaging marker prospectively proven to predict PD was described only as recently as 2010, when Iranzo and colleagues documented that dopaminergic functional imaging predicted neurodegeneration among patients with idiopathic RBD . This was confirmed in a second RBD cohort . Predictive value was confirmed in a non‐RBD population only in 2017, with the PARS study.…”
Section: Key Advances In the Last Decadementioning
confidence: 99%
“…A recent Chinese study comparing patients with iRBD to PD and controls found both motor and non‐motor deficits in patients with iRBD 69 . Involvement of olfaction, gastrointestinal, and cardiovascular functions has been confirmed in other studies of iRBD and found to be predictive of impending conversion to neurodegenerative disease 70 , 71 …”
Section: Idiopathic Rbd As a Predictor Of Neurodegenerationmentioning
confidence: 87%
“…However, progression in the prodromal phase is an even greater challenge, as there are currently no clinical or biochemical markers to predict who will convert and when. First studies imply that imaging markers may be helpful to better understand individual progression of the neurodegenerative process with Dopamin‐Transporter‐Imaging using single photon emission computed tomography (DATScan) being promising for individuals close to motor manifestation . Still, long follow‐ups will be needed for clinical studies making this rather complex and costly imaging tool unlikely to be implemented in the routine for application in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…First studies imply that imaging markers may be helpful to better understand individual progression of the neurodegenerative process with Dopamin-Transporter-Imaging using single photon emission computed tomography (DATScan) being promising for individuals close to motor manifestation. 90,91 Still, long follow-ups will be needed for clinical studies making this rather complex and costly imaging tool unlikely to be implemented in the routine for application in the general population. Magnetic resonance imaging markers, which are increasingly promising on a group level as biomarkers for a prodromal state, have not classified as progression markers yet.…”
Section: Targets From Epidemiological Studies and Symptomatic Therapymentioning
confidence: 99%